Instructional design innovation in distance learning to improve student learning performance - Sagoro, Endra Murti; Warsono, Sony; Mustakini, Jogiyanto Hartono; Handayani, Wuri (LPMPP Universitas Negeri Yogyakarta, 2025)
This study investigates the application of instructional design innovations to improve student learning performance, focusing specifically onthe learning materials and teaching methods. The introductory accounting course was taken as the object of study because it is a compulsory subject at the Faculty of Business. Cognitive load theory (CLT) and scaffolding theory were employed in explaining and developing the hypotheses. This study examined student learning performance gaps on instructional design innovation through learning materials (mathematics vs. traditional) and scaffolding (soft vs. hard). This study adopted a 2 x 2 experimental design involving 166 new undergraduate students at Universitas Negeri Yogyakarta in Indonesia. The research findings demonstrated that the instructional design of mathematics-based accounting learning effectively improves student learning performance during distance learning. Meanwhile, the use of scaffolding did not generate any significant differences in student learning performance during distance learning.